My Two Cents on Changing Times - David M. Becker (Washington University Law Quarterly, 1998)
In this Article, I provide an overview of changes that have taken place at Washington University over the course of his 35 years of tenure, including changes in the curriculum, the makeup of the faculty and student bodies, and the law school building itself.
Keywords: Law -- Study & teaching; Law schools -- Curricula; Washington University. School of Law